Multiseptate gallbladder accompanied by an incomplete annular pancreas in a 19-year male patient: A case report - Andrej Nikolovski, MD, PhD; Shqipe Misimi, MD; Stanko Trpeski, MD; Zvonko Atanasov, MD, MSc (Radiology Case Reports, 2025)
Multiseptate gallbladder (MG) is a rare congenital malformation that may occur as an isolated anomaly or in conjunction with other abnormalities of the pancreaticobiliary, urinary, and gastrointestinal systems. The coexistence of MG with an annular pancreas is an exceedingly rare phenomenon. The diagnosis is typically established using abdominal ultrasound; however, further imaging modalities are often required to delineate the detailed anatomy and to identify any associated anomalies within the pancreaticobiliary system. We present a case of a symptomatic MG associated with an incomplete annular pancreas. This case underscores the importance of considering additional congenital anomalies in patients diagnosed with MG, as such associations may influence clinical management and outcomes.